Where have I lost my appendix? An unusual finding of acute appendicitis within an irreducible umbilical hernia sac. Case report.: Acute appendicitis in an umbilical hernia. - Pilia, Tiziana; Murzi, Valentina; Locci, Eleonora; Gessa, Emanuela; Corronca, Federico; Frongia, Federica; Podda, Mauro; Pisanu, Adolfo (Acta Biomedica Atenei Parmensis, 2024)
An umbilical hernia is the bulging of the omentum, preperitoneal fatty tissue, or bowel out of the abdominal cavity through the umbilical orifice. The incidence of umbilical hernia follows that of the inguinal and the crural hernia. It is frequent in women, obese patients, smokers, and patients with ascites. It is an often asymptomatic pathological entity, which, however, can become complicated by giving rise to bowel obstruction, irreducibility, and ischemia. The finding of the appendix within an inguinal or a femoral hernia is called Amyand’s hernia and De Garengeot’s hernia, respectively. The presence of the appendix inside an umbilical hernia is instead a rare event. To date, 11 cases of complicated umbilical hernia containing the appendix have been described in the literature. We present the case of a patient admitted to our surgical department for an acutely irreducible umbilical hernia. Due to the failure to reduce the hernia with taxis and the persistence of hernia incarceration, the patient underwent laparoscopic surgery. Intraoperatively, catarrhal appendicitis was found within the hernia sac. After the appendectomy and the reduction of the hernia content, a laparoscopic mesh repair (IPOM) was performed. The post-operative course was uneventful, and the discharge happened on the second post-operative day. This case report demonstrates the importance of promptly intervening in complicated umbilical hernias. The laparoscopic technique has shown to be safe because, in the absence of intra-abdominal enteric leakage, mesh repair by laparoscopy offered the advantage of an early post-operative recovery and time to return to daily activities